Salgado Gómez, M. (2021). Indios altivos e inquietos: Conflicto y política popular en el tiempo de las sublevaciones: Riobamba en 1764 y Otavalo en 1777. FLACSO – Abya Yala - Díaz Palacios, Andrea (2025)
The book “Indios altivos e inquietos. Conflicto y política popular en el tiempo de las sublevaciones: Riobamba en 1764 y Otavalo en 1777” offers an analysis grounded in social and political history, along with several insights from cultural history, aimed at reinterpreting at least two concepts debated in Latin American historiography and the social sciences: Indian/Indigenous and popular uprisings. The review emphasizes the author’s methodology, theoretical approaches, dialogues, and empirical findings based on primary sources. It also provides the structure of the work and a critical summary of the book’s seven chapters.